Paw patrol. Winter rescues [videorecording (DVD)] - Chapman, Keith, 1958- (PAW patrol, 2014)
Paw Patrol is on a roll, even through the ice and snow, in these seven wintry missions, including a double-length adventure to save Christmas! From a ski-lift rescue to tracking down a snow monster, no job is too big and no pup is too small. Plus, see how Rubble first joined the team by helping out in a snowy situation!